Design, Development and Performance Evaluation of ICAR-CIRCOT Briquette Based Crematorium - SHUKLA, S. K.; ARUDE, V. G.; PATIL, P. G.; RAJA, A. S.M.; BHARIMALLA, A. K.; PATIL, D. U. (Cotton Research Journal, 2021)
In this work, a briquette-based crematorium, as an alternative to the firewood cremation process has been designed, developed and extensively evaluated at a crematorium site. The two types of crematoriums having a rectangular and a trapezoidal shaped cage were designed and developed and compared with the traditional firewood cremation process. An electrically operated centrifugal fan was used to supply the forced air draft at the bottom and two long sides of the crematorium. The trapezoidal shaped crematorium was found to be optimum shape requiring 200 kg briquettes and 3-4 h duration for complete cremation of a dead body. The developed innovative crematorium has been found to be very efficient in cremation and is environment friendly. All social customs like mukhagni, kapakriya, etc. can be performed easily in the developed crematorium. The use of forced air draft system not only brings down emissions and smoke formations to very low level but also reduces the requirement of camphor, kerosene/diesel and ghee needed for fire initiation to almost zero. Due to supply of adequate air for combustion, the temperature was found to go as high as about 1000 0C within 30 min of igniting fire. Thus, briquettes burnt efficiently and effectively during entire cremation process resulting into smokeless, foul smell free cremation. The promotion of briquettes for cremation would result in value addition to biomasses, specially cotton stalks readily available in India leading to increase in farm income and employment generation in rural areas.